Fatigue behavior of 3-D orthogonal woven composite with silane modification - Yi Zhang; Xiaoping Gao; Nannan Tao (Materials Research Express, 2020)
As key part in wind turbine, the blade is a vital component for energy transformation. Fiber reinforced composite has advantage of light weight, large specific strength and specific stiffness, which has been used in wind turbine blade. In order to avoid delamination of conventional laminate and debonding between fiber and epoxy, the silane modification composite specimen reinforced with 3-D orthogonal woven fabric/epoxy was prepared using vacuum assisted resin transfer molding (VARTM) for blade. As for fatigue experiment, the critical stress levels corresponding to micro-crack initiation and failure of composite were obtained by combining of acoustic emission technology and quasi-bending experiment. The fatigue behavior of 3-D orthogonal woven composite with silane modification was experimental evaluated based on the minimum and maximum stress levels. The fatigue behavior, such as S-N curve, stress-strain behavior and stiffness degradation behavior were analyzed. The result will provide the basis for investigation of bending behavior with nondestructive tests and set of stress level in bending fatigue experiment.